Performance of dye-sensitized solar cells with mixed three natural pigments and reduced graphene oxide as a counter electrode - Eka Cahya Prima; Prima Fitri Rusliani; Endi Suhendi; Brian Yuliarto (Results in Optics, 2024)
This work overviews the effect of combining three natural dyes as a photosensitizer for dye-sensitized solar cells (DSSC). Reduced graphene oxide in this work was used as a Pt-free counter electrode. The dyes consist of curcuminoid (Curcuma longa), chlorophyll (Justicia gendarussa), and anthocyanins (Clitoria ternatea). The effect of absorbance spectrum, Light Harvesting Efficiency (LHE), bandgap energy, and performance of DSSC were also studied. From the result, combination dyes have a broader absorbance spectrum and LHE than a single dyes solution, while the redox potential of the dye produces a similar gap energy (HOMO/LUMO) due to the solvent used to extract the dye, which is around 1.76–1.79 eV. The best result was achieved by a combination of three dyes, Yellow-Green-Blue, which has a short-circuit current density (Jsc) of 6.50 mA/cm2, an open-circuit voltage (Voc) of 0.94 V, a fill factor of 31.2 %, and efficiency of 1.91 %. The performance of the DSSC is not only due to a large amount of photon energy absorbed and adsorbed on the TiO2 surface and the fast electron diffusion rate due to the large LHE and narrow gap energy. Therefore, combining natural dye and using rGO as the counter electrode can improve the performance of DSSC optimally.